Kelimpahan Populasi dan Serangan Penggerek Batang Padi pada Tanaman Padi di Kabupaten Tabanan - LUH TINA ARYANTINI; I WAYAN SUPARTHA; I NYOMAN WIJAYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2015)
ABSTRACT Population Abundance and Rice Stem Borer Attack on Rice in Tabanan Regency Tabanan Regency is rice production center in Bali Province. In terms of rice production in 2009 Tabanan Regency can produce 242.000 tons of grain per year, still rice production in the field has many obstacles, one of which is the rice stem borer can attack plants in the vegetative phase and the generative phase. It is necessary for the proper control measures, through an ecological approach and monitoring system to control rice stem borer in the field. The pattern of population growth which include diversity and population dynamics of the rice stem borer in the field, it is helpful for decision-making in determining control strategies appropriate to the circumstances on the ground pests. Found four species of rice stem winches in Tabanan Regency. The fourth species is Scirpophaga incertulas Walker, Sesamia inferens Walker, Chilo suppressalis Walker, and Chilo polychrysus Meyrick. S. incertulas is the dominant species found at each altitude. Rice stem borer species diversity is low <1.5, The value of the index of similarity between the study site reached a value of 86 % and 100 % . The structure of the rice stem borer populations between egg , larva , pupa and imago fluctuate every stage of plant development and reached its peak at the age of  rice 2 Weeks after planting egg stage , 4 Weeks after planting on larval and imago , 5 Weeks after planting at the pupa stage. The highest population abundance indicated S. incertulas at an altitude <250 (0-250) masl (meters above sea level), with the highest attack percentage at a height <250 (0-250) masl.   Keywords: Rice stem borer, species diversity, abundance, percentage.